(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This paper presents an example of Software Architecture and design for online registration system. Software design is an early phase of the Software Development Life Cycle (SDLC). During this phase, software designers model the system and assess its quality so that improvements may be made before the software goes into the production phase. The goal of software design is to build a model that meets all customer requirements and leads to successful implementation. As software systems continue to grow in scale, complexity, and distribution, their proper design becomes extremely important in software production. The architecture design representat ion is derived from the system requirement specification and the analysis model. Multi tier architecture is commonly used for distributed systems. It usually consists of three element types: client, middleware server, and data server. The Unified Modeling Language ( used to model the problem domain; describe the user requirements; identify significant architecture elements during software design, such as classes and objects; describe behavior and interactions among these elements; and organize the softw are structure, specify its constraints, describe the necessary attributes, and more.